ANALISIS WACANA GENDER SARA MILLS CERPEN MAAFKAN AKU TERLAHIR PEREMPUAN KARYA JINGGA LESTARI - Wasis Sirutama; Yusak Hudiyono (Jurnal Inovasi Penelitian, 2023)
Abstract Short stories, as the name implies, show a very short nature in both the events that are disclosed and the contents of the story, including the number of actors and the number of words used. Sara Mills examines how women are presented in texts, whether in novels, photographs, or the news. It is this injustice and bad portrayal of women that are the main targets of Mills' writing. This study aims to examine the value of feminism by looking at the position of the subject-object and the position of the writer-reader in Sara Mills' study. This type of research is qualitative. Qualitative analysis here uses descriptive language, which tells, describes, gives, analyzes, and interprets. The results of this study reveal the position of the narrator's subject in the short story I'm Sorry I Was Born a Woman by Jingga Lestari, namely the author. The position of the object told in the short story Forgive Me to Be Born a Woman by Jingga Lestari is the character "I" as a woman. The author's position in the short story Forgive Me, I Was Born a Woman by Jingga Lestari positions herself as a woman. The reader positions himself in the story based on the events disclosed by the author.